Sustaining Commitment to Social Responsibility: Renewing the Ethical Basis of the Quality Agenda in the Education of Adults - Paul Armstrong (Adult Education Research Conference, 1999)
This paper seeks to extend the notion of quality in higher education by considering the agenda for environmental sustainability and underlying ethical practices. Education institutions should be committed to the extended version of quality, and should not lose sight of the importance of commitment and social responsibility in the drive for a quality kitemark.